Philosophical perspectives towards curriculum - Tamang, Yam Bahadur (Innovative Research Journal, 2023)
The curriculum is the backbone of the education system of any country. Philosophy and curriculum are interrelated, philosophy provides guidelines for curriculum development and it helps to select the valid and significant content, appropriate instructional methods, materials, teaching-learning activities, and evaluation process in the curriculum. This is a knowledge-based article and descriptive. In this article, I have discussed the four major philosophies and four major educational philosophies related to curriculum. In preparing for this article I have used published books, and online documents for the study sample and data collection tools.